ADAPTATION OF THE CHILD TO THE PRESCHOOL INSTITUTION - Sanoat Zohidova; Gavkhar Ruzieva (International Journal on Integrated Education, 2021)
The question of whether to send a child to a kindergarten or not to give rises to almost every family with small children. Some families are forced to do this, but they are reluctant to take this step due to the cramped economic situation, when all adults work and there is no one to leave the child at home with. Other families adhere to the point of view that the modern child should be in the environment of peers, acquire the social experience that will facilitate his transition to school. Finally, there are parents who highly appreciate the educational potential of a preschool institution and therefore consciously do not want to limit the upbringing of their own child to the family.